2008
DOI: 10.3181/0712-rm-328
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Levels of MCP-1 and Eotaxin Provide Evidence for an Immunological Basis of Fibromyalgia

Abstract: Fibromyalgia (FMS), a predominantly female (85%) syndrome, affects an estimated 2% of the US population with skeletal muscle ache, fatigue, headache, and sleep disorder. The pathogenesis of FMS is unknown and there is no laboratory test for diagnosis. In this study, plasma levels of 25 cytokines and chemokines in 92 female patients with FMS and 69 family members were measured compared to 77 controls. Trans-endothelial migration of normal leukocytes in response to FMS plasma and the cytokine profile of human my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 44 publications
11
104
0
Order By: Relevance
“…A study of 92 patients with fibromyalgia has shown that these patients have higher MCP-1 levels than controls and that their sera induce increased migration of macrophages. Interestingly, the levels of these cytokines did not differ when obese and non-obese patients with fibromyalgia were compared, a finding similar to the present study (35).…”
Section: Discussionsupporting
confidence: 79%
“…A study of 92 patients with fibromyalgia has shown that these patients have higher MCP-1 levels than controls and that their sera induce increased migration of macrophages. Interestingly, the levels of these cytokines did not differ when obese and non-obese patients with fibromyalgia were compared, a finding similar to the present study (35).…”
Section: Discussionsupporting
confidence: 79%
“…Monocyte chemoattractant protein-1 (MCP-1/CCL2) and eotaxin (CCL) have both been reported to be elevated in plasma of FMS patients (Zhang et al, 2008). MCP-1 also plays a pivotal role in inflammatory myopathies; myoblasts treated with MCP-1 or eotaxin secrete significant amounts of interleukin-1b (IL-1b) (Zhang et al, 2008).…”
Section: Pathogenesismentioning
confidence: 99%
“…MCP-1 also plays a pivotal role in inflammatory myopathies; myoblasts treated with MCP-1 or eotaxin secrete significant amounts of interleukin-1b (IL-1b) (Zhang et al, 2008). In addition, a study using a rat model to evaluate the involvement of MCP-1 in stress-induced chronic pain showed that MCP-1 induces longlasting muscle hyperalgesia and a state of latent chronic sensitization to other allogenic substances through activation of its high-affinity receptor, CCR2, located on the peripheral terminals of IB41 nociceptors (Alvarez et al, 2014).…”
Section: Pathogenesismentioning
confidence: 99%
“…The IL-8 has been found to be elevated in both serum and plasma of patients with FM [10,53,91,[97][98][99]100,106,107,111,113]. However, while most studies which studied the role of IL-8 in fibromyalgia, found it high, there are also authors who have not indicated variations of this inflammatory cytokine in the blood of patients with FM [102,105,110,112,114,115].…”
Section: Cytokines In Fmmentioning
confidence: 99%